Interpreting Europe and US Labor Markets Differences: The Specificity of Human Capital Investments - Etienne Wasmer (Institute for the Study of Labor (IZA), 2002)
This paper suggests that in the US context, workers tend to invest in general human capital especially since they face little employment protection and low unemployment benefits, while the European model (generous benefits and higher duration of jobs) favors specific human capital investments. This conjecture provides, among other things, a rationale for differences in labor mobility and reallocation costs, which are typically ignored in American ?International Trade? textbooks while considered as extremely large in the public debate in Europe. The main argument is based on a fundamental property of human capital investments: they are not independent of the aggregate state of labor markets, and in particular, frictions and slackness of the labor market raises the returns to specific human capital investments relative to general capital investments. This is a property that Becker?s seminal contributions could not envisage in the context of perfect labor markets. Two sets of implications are then derived: on one hand, mobility costs are high in Europe and transitions between steady-states has especially strong adverse effects. Jobs endogenously last longer in Europe than in the US, but when they are destroyed, the welfare loss for workers is higher. On the other hand, in the steady-state, European workers, ceteris paribus, are more efficient. In terms of transaction costs, the US pay on average higher search/hiring costs in the labor market, and smaller training costs, so that the welfare implications of each type of economy are a priori ambiguous: no model dominates the other one, and each one has its own coherence, although the European one is more fragile when macroeconomic conditions change.
Keywords: J30; J63; 330; training; specific human capital; general human capital; unemployment; matching; Arbeitsmarkt; Bildungsinvestition; Humankapital; Arbeitsmobilität; Arbeitslosigkeit; Kosten-Nutzen-Analyse; Wohlfahrtseffekt; Vergleich; Theorie; Vereinigte Staaten; Europa